PENGARUH PERBEDAAN UKURAN MATA PANCING TERHADAP HASIL TANGKAPAN IKAN DASAR (DEMERSAL FISH) DENGAN ALAT TANGKAP RAWAI DASAR (BOTTOM LONG LINE): The Influence of Fishing Differences On Base Fish Catches (Demersal Fish) With Basic Long Fishing Green (Bottom Long Line) - Endang Ariani; Aryani Rahmawati; I Nyoman Budi Satriya; Hamid Hamid (Yayasan Al-Amin Qalbu, 2023)
Bottom fish (Demersal fish) are fish whose habitat lives in coral and at the bottom of rocky waters, staying silent in holes to wait for prey. The distribution and abundance of bottom fish is strongly influenced by the environmental conditions of the waters as well as the oceanography. Potential fishing areas are waters where there are many fish in schools and it is possible to catch them with certain fishing gear. Bottom long line fishing gear is a fishing gear made of a set of long lines (line fishing) intended to catch various types of bottom (domersal) fish and so on in large sizes and quantities. one type of basic fishing gear that is quite productive. This study aims to determine the size of the most productive hook (hook) and to determine the types of bottom fish caught using bottom long line fishing gear.